MỘT PHƯƠNG PHÁP ĐỊNH LƯỢNG PHÂN CẤP NGUY CƠ TRƯỢT ĐẤT ÁP DỤNG CHO THỊ TRẤN CỐC PÀI - HUYỆN XÍN MẦN-TỈNH HÀ GIANG - Hoàng, Nguyễn Văn; Thành, Nguyễn Quốc; Công, Lê Thành (Vietnam Journal of Earth Sciences, 2012)
A method of landslide vulnerability mapping applied to Xin Man district town, Ha Giang province Landslide is a result of varied reasons, especially of three factors: increase of soil unit weight, decrease of cohesion and friction angle and increase of pore water pressure. Landslide vulnerability is a generalized function of these three factors, slope angle and soil thickness. Highly accurate landslide vulnerability zonation may be carried out through quantitative determination of this generalized function. This landslide vulnerability zonation methodology had been applied to Xin Man town-Ha Giang province. The introduced methodology can be effectively applied to other study areas and serve as one of fundamentals of land use planning in mountainous areas as well as to propose effective landslide prevention measures.